2017
DOI: 10.1016/j.celrep.2017.03.080
|View full text |Cite|
|
Sign up to set email alerts
|

NLRP6 Protects Il10 Mice from Colitis by Limiting Colonization of Akkermansia muciniphila

Abstract: Summary Dysfunction in host immune responses and pathologic alterations in the gut microbiota, referred to as dysbiosis, can both contribute to the development of inflammatory bowel disease (IBD). However, it remains unclear how specific changes in host immunity or the microbiota cause disease. We previously demonstrated that the loss of the innate immune receptor NLRP6 in mice resulted in impaired production of IL18 and increased susceptibility to epithelial-induced injury. Here, we show that NLRP6 is importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
229
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 287 publications
(246 citation statements)
references
References 48 publications
16
229
1
Order By: Relevance
“…Strikingly, fecal microbiota analyses of these ex-GF mice showed an impact of Nlrp6 on intestinal ecology within two weeks. 23 These observations were similar to a previous study using an adult ex-GF approach, showing that the gut microbiota communities of ex-GF WT and Nlrp6 −/− mice diverged at three weeks after re-colonisation. 15 However, while this latter ex-GF study did not specify whether Prevotellaceae alterations previously observed in non-littermate WT and Nlrp6 −/− mice were reproduced, 15 Seregin et al.…”
Section: Nlrp6/asc Inflammasomes Do Not Shape the Commensal Gut Microsupporting
confidence: 90%
See 4 more Smart Citations
“…Strikingly, fecal microbiota analyses of these ex-GF mice showed an impact of Nlrp6 on intestinal ecology within two weeks. 23 These observations were similar to a previous study using an adult ex-GF approach, showing that the gut microbiota communities of ex-GF WT and Nlrp6 −/− mice diverged at three weeks after re-colonisation. 15 However, while this latter ex-GF study did not specify whether Prevotellaceae alterations previously observed in non-littermate WT and Nlrp6 −/− mice were reproduced, 15 Seregin et al.…”
Section: Nlrp6/asc Inflammasomes Do Not Shape the Commensal Gut Microsupporting
confidence: 90%
“…did not observe those reported effects on Prevotellaceae and rather found an increase in Akkermansia muciniphila in ex-GF Nlrp6 −/− mice. 23 These discordant observations in ex-GF mice illustrate that the nature of the donor SPF microbiota could determine potential host genetic effects on the gut microbiota in these experiments. Likewise, factors such as diet and the nature of the resident SPF microbiota composition may influence the impact of a host gene on the gut microbiota when investigated in different animal facilities.…”
Section: Nlrp6/asc Inflammasomes Do Not Shape the Commensal Gut Micromentioning
confidence: 98%
See 3 more Smart Citations